OPTIMALISASI MANAJEMEN ZAKAT BERBASIS DATA DALAM MENDUKUNG PENGENTASAN KEMISKINAN DI INDONESIA - Moh Agus Sifa' (JPSDa: Jurnal Perbankan Syariah Darussalam, 2026)
Zakat is an Islamic economic instrument with significant potential to support social welfare and poverty alleviation in Indonesia. However, previous studies have largely examined zakat management from institutional, normative, or digitalization perspectives separately, while limited research has integrated data-driven management as a comprehensive framework for optimizing zakat collection and distribution. This study aims to analyze the optimization of data-driven zakat management in supporting poverty alleviation in Indonesia and proposes an integrated perspective linking data utilization, digital technology, and mustahik empowerment. The study employed a qualitative approach using library research. Data were collected from scholarly books, journal articles, official reports of the National Board of Zakat (BAZNAS), publications of the Center for Strategic Studies of BAZNAS (Puskas BAZNAS), Central Bureau of Statistics (BPS) data, zakat regulations, and other relevant academic literature. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, encompassing data collection, data condensation, data display, and conclusion drawing. The findings reveal three main points: first, data-driven management can improve the accuracy and effectiveness of zakat collection and distribution; second, the utilization of digital technologies, including zakat information systems, Big Data, Artificial Intelligence, and Geographic Information Systems, strengthens evidence-based decision-making and the targeting of mustahik empowerment programs; and third, fragmented databases, limited data quality, human resource capacity, and data security remain major challenges. Practically, the findings provide a strategic basis for BAZNAS and Zakat Management Organizations to develop integrated, secure, and evidence-based zakat management systems that enhance institutional accountability and strengthen zakat’s contribution to sustainable poverty alleviation in Indonesia.